Analisis Dampak Lingkungan Kerja Fisik terhadap Kepuasan Kerja Karyawan pada PT. Pos Indonesia KCP Alue Bilie - Yanti, Darmi; Damrus, Damrus; Zhafira, Nabila Hilmy; Manan, Afni Abdul (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
This research investigates the influence of the physical work environment on the level of employee satisfaction at PT. Pos Indonesia KCP Alue Bilie. The focus of the analysis is evaluating the impact of the physical work environment on employee satisfaction, using qualitative research methods and involving several informants. The object of this analysis is the employee of PT Pos Indonesia KCP Alue Bilie. The research subjects were the condition of the physical work environment and the employees of PT Pos KCP Indonesia Alue Bilie, numbering only 2 people. Determining the sources using purposive sampling technique, 2 sources were obtained. Data collection techniques use interviews, observation and documentation. The results of the research are that the availability of physical facilities, such as air conditioning, lighting, and also wages based on position, as well as the quality of team work can have an impact on employee satisfaction at work. It was concluded that employees at PT. Pos Indonesia KCP Alue Bilie has achieved an adequate level of satisfaction with the physical work environment, as seen from their ability to complete tasks on time, even though these tasks are considered a burden on the company.